CRIME INVESTIGATIONS OF ‘CHILD ABUSE MATERIAL’: CHALLENGES AND OPPORTUNITIES POSED BY DIGITAL TECHNOLOGIES - Eneman, Marie (AoIR Selected Papers of Internet Research, 2020)
The increased digitalisation of society has profoundly changed the circumstances for people with a sexual interest in children to engage in the production, distribution and consumption of child abuse material. In addition, digital technologies enable contact and communication with other like-minded individuals sharing the same sexual interest in children and also facilitate new forms of getting in contact with children (potential victims). Child abuse material (sometimes also referred to as child pornography) refers to documented material depicting the sexual abuse and/or sexual exploitation of a child (or children). The overall purpose with this study is to explore the practices where crime investigations of child abuse material occur within the Swedish police authority. This research in progress paper will reflect on what challenges and opportunities police officers do encounter when investigating child abuse material in relation to digital technologies? The involved technology will be investigated in relation to technological affordance and empirically the study is based upon qualitative interviews with police officers.